Enteral Sodium Chloride Supplementation and Fluid Balance in Children Receiving Diuretics - Laura Ortmann; Teri J. Mauch; Jean Ballweg (MDPI AG, 2022)
The use of sodium chloride (NaCl) supplementation in children being prescribed diuretics is controversial due to concerns that supplementation could lead to fluid retention. This is a single-center retrospective study in which fluid balance and diuretic dosing was examined in children prescribed enteral NaCl supplements for hyponatremia while receiving loop diuretics. The aim of this study was to determine whether significant fluid retention occurred with the addition of NaCl. Fifty-five patients with 68 events were studied. The median age was 5.2 months, and 82% were hospitalized for cardiac disease. Daily fluid balance the seven days prior to NaCl supplementation was lower than the seven days after, with measurement of: median 17 mL/kg/day (7-26) vs. 22 mL/kg/day (13-35) (p = 0.0003). There was no change in patient weight after supplementation (p = 0.63). There was no difference in the median loop diuretic dose before and after supplementation, with the diuretic dose in furosemide equivalents of 3.2 mL/kg/day (2.3-4.4) vs. 3.2 mL/kg/day (2.2-4.7) (p = 0.50). There was no difference in the proportion of patients receiving thiazide diuretics after supplementation (56% before vs. 50% after (p = 0.10)). NaCl supplementation in children receiving loop diuretics increased calculated fluid balance, but weight was unchanged, and this was not associated with an increase in diuretic needs, suggesting clinicians did not consider the increase in fluid balance to be clinically significant.